Peran Teknologi Perangkat Pembentuk Artificial Intelligence dalam Novel Traveline Past Karya Luna Torashyngu - Muhammad Rasyid Nurrohman; Eva Dwi Kurniawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The aim of this research is to explore the role of Artificial Intelligence (AI) device technology in supporting everyday human life, especially in Luna Torasyngu's novel